Best Answer

y and x cannot both be zero and still satisfy the equation.

Q: What equals 6 equals 3x-2y equals to if y is 0 and x is 0?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Related questions

2y-6=3x2y-3x-6=0-3x-6=-2y3/2x+3=yy-inercept= 3slope= y(2)-y(1)/x(2)-x(1)= 6-3/2-0= 3/2

No because in this equation x = -6 -6--6 = 0

X + (-6) = 0 x = 6 6 is the answer

(3 * 3)(2 * 5) (9)(10) 90

anything x 0 = 0

6

(x, y) = (-6, 0)

30 x 0

x^2+5-6=0 (x+6)(x-1)=0 x=1,-6

x = 0

0

y = 6